Comparison Of Flavonoid Content And Α-Amylase Inhibition Activity Of Ethanol Extracts From Compound Garlic (Allium Sativum L), Black Garlic, And Single Garlic - Dwi Nurul Khotimah; Danang Raharjo; Bagas Ardiyantoro (International Journal of Health Engineering and Technology, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin metabolism, and it remains one of the leading global health problems. One promising therapeutic strategy for diabetes management is the inhibition of digestive enzymes such as α-amylase, which plays a role in carbohydrate breakdown. Flavonoids, as natural bioactive compounds found in plants, have been reported to act as effective enzyme inhibitors. This study aims to compare the flavonoid content and α-amylase enzyme inhibitory activity of ethanol extracts from compound garlic (Allium sativum L.), black garlic, and single garlic. The extraction process was carried out using maceration with 96% ethanol solvent, followed by flavonoid content determination using UV-Vis spectrophotometry, while α-amylase inhibitory activity was tested using the Fuwa method. The results demonstrated that black garlic extract contained the highest flavonoid concentration, reaching 48.874 mg QE/g, compared to single garlic (40.561 mg QE/g) and compound garlic (35.943 mg QE/g). In addition, black garlic exhibited the strongest α-amylase inhibitory activity with the lowest IC₅₀ value of 32.390 ppm, indicating a higher potency compared to the other garlic extracts. These findings suggest that the fermentation process in black garlic enhances its flavonoid profile and bioactivity. Therefore, black garlic has significant potential as a natural antidiabetic agent and could be further explored as a functional food ingredient or herbal therapy for diabetes prevention and management.